The psychological process and emotional cognition of children's tourism experiences in Chinese family culture - Guo, Xuanxuan; Liu, Tao (Frontiers in Public Health, 2022)
Family cultural environment affects children's cognitive development and socialization process. Different family cultural environment will lead to differences in children's tourism experience. The current research demands a shift from the child’s perspective to that of exploring the children.In response to this, grounded on the cognitive development theory, this paper from the perspective of the unforgettable parent-child tourism experience among children, the children's drawings are used to project the patterns of tourism elements, people, activities, scenes, and colors that children perceive from the trips. Furthermore, the relationship between children tourism experience and family culture is analyzed through interviews with children, combined with cultural psychology. Results show that children's perception of elements changes from the macro level to the micro level and the contents they perceive change from concrete to abstract. In addition, children have an acute perception of people and are impressed by the novelty of activities during trips, and they can experience changes in travel scenes and prefer bright and vibrant colors during trips. Children's high desire for knowledge and curiosity during trips is conducive to children's development of interpersonal and competence confidence, which in turn contributes to the enhancement of their emotional cognition. Therefore, it is recommended to design appropriate tourism products that combine the characteristics of children's experiences when offering parent-child travel programs, and upgrade the market of parent-child tourism experiences through novel activities.